2011
DOI: 10.1111/j.2044-8333.2010.02002.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement in extreme violence and violence‐related trauma: A review with relevance to young people in custody

Abstract: Purpose. This review is concerned with the points of contact between two diverse literatures: first, the association between childhood abuse and the development of violent conduct; second, the effects of involvement in the perpetration of acts of violence.Method. The empirical literature in the two areas of concern is considered along with complementary explanations for the extant evidence.Results. There is a weight of evidence indicating that childhood abuse is associated with later violence alongside a liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 89 publications
(125 reference statements)
0
15
0
Order By: Relevance
“…Miller and Najavits (2012) discuss a key point for the criminal justice system and the role of trauma-informed care in prison populations, and they put forward the centrality of trauma in the lives of inmates proposing the components of what they name trauma-informed correctional care (TICC). Because prison settings are per se a caveat of unavoidable triggers such as frequent discipline from authority figures and restricted movement (Owens, Wells, Pollock, Muscat & Torres, 2008) that are likely increase trauma-related behaviours and symptoms difficult for prison staff to manage.…”
Section: Limitations Of Current Literaturementioning
confidence: 99%
“…Miller and Najavits (2012) discuss a key point for the criminal justice system and the role of trauma-informed care in prison populations, and they put forward the centrality of trauma in the lives of inmates proposing the components of what they name trauma-informed correctional care (TICC). Because prison settings are per se a caveat of unavoidable triggers such as frequent discipline from authority figures and restricted movement (Owens, Wells, Pollock, Muscat & Torres, 2008) that are likely increase trauma-related behaviours and symptoms difficult for prison staff to manage.…”
Section: Limitations Of Current Literaturementioning
confidence: 99%
“…In addition, Verona & Carbonell (2000) speculate that their OV offenders may have responded with 'extreme' violence due to interpersonal and relationship stress. Other authors have emphasized the role that abusive or nonmutual relationships and experiences may have in eliciting extreme violence particularly when accompanied by elevated levels of distress (Heide & Solomon, 2009;Welfare & Hollin, 2012). Thus, it is important to recognize the varying quality of even 'close' peer relationships that may promote the risk of violence as well as abusive relationships that may initially contain potentially violent female offenders in the short term.…”
Section: How Does This Study Compare With Previous Research?mentioning
confidence: 95%
“…This is of particular importance for those custodial institutions and professionals responsible for delivering offender treatment and risk management programmes (Covington & Bloom, 2003;Van Voorhis et al, 2008;Welfare & Hollin, 2012). Downloaded by [University of Tennessee, Knoxville] at 12:27 04 June 2016…”
Section: Correlates Of Violent Female Recidivismmentioning
confidence: 97%
“…For example, research has found that traumatic experiences can lead to a general lack of trust of adults (Welfare and Hollin ; Wright and Liddle ). It has also been found that offenders simply want to avoid thinking about, or discussing, painful experiences and events (see DSM, Criterion C, American Psychiatric Association ; Welfare and Hollin ; Wright and Liddle ). As Gareth noted: ‘I hate talking about it, just reminds me about it really’.…”
Section: How To Best Identify and Support Traumatised Young Peoplementioning
confidence: 99%